Efforts of Bhabinkamtibmas Pati Kota Police Through the Activated Sambang Door-to-Door System to Prevent Curanmor Criminals in the Legal Area of Pati Polresta - Riawan, Made (Advances in Police Science Research Journal, 2024)
This study aims to determine the implementation of the door-to-door system carried out by Bhabinkamtibmas Polsek Pati Kota to prevent criminal acts of theft and to determine the competency of the organizational resources of the Bhabinkamtibmas Unit. The type of research used in this study is empirical juridical. The data collection techniques used are observation, interview, and documentation studies. The analysis technique used in this study is first collecting, then reducing the data obtained, then presenting the data, and finally drawing conclusions. The theories used in this research are SWOT Theory, POAC Theory, and 5M Management Theories, such as Man, Money, Material, Market, and Machine. The results of this study include: 1) Implementation of a door-todoor system by Bhabinkamtibmas to prevent theft in the jurisdiction of the Pati Police, which refers to the Chief of Police regulation number 7 of 2022. In implementing this activity, there are still deficiencies, including in the field of planning, such as not mentioning the name of the activity which will be carried out and the material is not prepared, in organizing for example, Bhabinkamtibmas who do not have an educational background, in the field of implementation there are indicators that are not or have not been fulfilled, as well as in the field of supervision such as not regularly holding meetings. 2) The factors that influence the implementation of the door-to-door system conducted by Bhabinkamtibmas are Internal factors and external factors. Internal factors such as the quality and quantity of personnel, as well as the infrastructure that, supports the performance of Bhabinkamtibmas. External factors such as getting support from the community